Analysis of cumulative live birth rate and perinatal outcomes in young patients with low anti-müllerian hormone levels using two ovulation promotion protocols: A cohort study - Li, Zhen; Jia, Ruolin; Wang, Kexin; Zhang, Junwei; Ren, Bingnan; Guan, Yichun (Frontiers in Endocrinology, 2022)
To compare the cumulative live birth rates and perinatal outcomes of young IVF/ICSI patients with low AMH levels on the GnRH-ant regimen with those on the PPOS regimen. To retrospectively analyze 798 patients underwent IVF or ICSI between January 2015 and December 2020 at the Third Affiliated Hospital of Zhengzhou University. A total of 798 cycles of complete clinical data of patients underwent IVF or ICSI at the Reproductive Medicine Center of Zhengzhou University Hospital between January 2015 and December 2020 and were eligible for AMH < 1.2 ng/ml at age < 35 years. Group A1: very low AMH level (AMH < 0. 5 ng/mL) and GnRH-ant Group A2: very low AMH level and PPOS ; Group B1: low AMH level (0. 5 ng/mL ≤ AMH < 1. 2 ng/mL) and GnRH-ant; Group B2: low AMH level and PPOS regimen.At very low AMH levels , the CLBR of the GnRH-ant was not different from that of the PPOS , LOW AMH Statistics showed that the CLBR of the GnRH-ant was higher than that of the PPOS.Logistic analysis showed that in group A: the younger the female partner the higher the CLBR the more AFC the higher the CLBR Group B: the higher the number of good quality embryos, the higher the CLBR compared to both regimens,ANT was able to increase The analysis of group A showed that the ant had a shorter TTP than the PPOS , however, the PPOS had a lower cost of ovulation . The GnRH-antin group B had a shorter TTP than the PPOS regimen and there was no difference in the cost of ovulation. In the analysis of perinatal outcomes, there were no significant differences in preterm, low birth weight, very low birth weight and pregnancy complications between the four groups.For patients with very low AMH levels GnRH ant is comparable to the PPOS in terms of CLBR outcomes. In young patients with low AMH levels , the GnRH ant is more appropriate to improve CLBR and perinatal outcomes are similar for both regimens.